Physical Characteristic, Chemical Composition and Organoleptic Test of Merawang Chicken Egg Fed with Omega-3 Supplementation Diet - Iman Rahayu HS (Jurnal Teknologi dan Industri Pangan, 2003)
Chicken egg is a good quality animal protein source. The quality of the egg can be improved with spesific feeding, such as omega-3 supplemented diet. Merawang chicken is one of local Indonesian chicken domesticated at Bangka Island, South Sumatera, and popular as a layer bird. The aim of this research was to study the effect of omega-3 supplementation on the physical characteristic, chemical composition and organoleptic test of Merawang chicken eggs. One hundred and thirty six eggs (73 eggs were control and 63 eggs was omega-3 suplemented) were collected from 64 Merawang chicken for eleven weeks. Feeding were arranged isonitrogenous (15.8%) and isocaloric (2650 kkal/kg), and fed ad libitum. Omega-3 feeding was produced from fermentation of soybean waste (ampas tahu) and mold (Rhizopus oligosporus), then mixed with sea fish oil waste (1:1, w/w). The result showed that no significant effect of the treatment on physical characteristic parameter. Omega-3 eggs significantly (P